Prospects of Immunology Education and Research in Developing Countries - Kwarteng, Alexander; Sylverken, Augustina; Antwi-Berko, Daniel; Ahuno, Samuel Terkper; Asiedu, Samuel Opoku (Frontiers in Public Health, 2021)
The burden of infectious disease in developing countries is substantially higher than in developed nations. Reasons include poor health care infrastructure and deficiencies in public understanding of infectious disease mechanisms and disease prevention. While immunology education and research have an enviable role in understanding host-pathogen interactions, training programs in immunology remain fully integrated into the curricula of higher institutions, and by extension, to high schools of developing nations. Therefore, we discussed the need to make major investments in immunology research and research training into biomedical science teaching curricula, particularly in developing countries